Demeaning extrinsic motivation leads to increased perceptions of hypocrisy - Yan, Liuxin; Emil Chai, Valentino; Chi Yam, Kai (Organizational behavior and human decision processes, 2024)
•Individuals may choose to demean extrinsic motivation as an impression management tactic to signal their intrinsic motivation.•Demeaning extrinsic motivation ironically leads to increased perceptions of hypocrisy, compared to demeaning other negative behaviors or explicitly expressing extrinsic motivation.•Individuals with a high job calling orientation are less prone to the negative effects of demeaning extrinsic motivation.•Individuals with a high socioeconomic status (SES) are seen as especially hypocritical when demeaning extrinsic motivation. People who are extrinsically motivated are negatively stereotyped and are viewed less positively compared to those who are intrinsically motivated. As a result, individuals can strategically express their intrinsic motivation as an impression management tactic to gain more favorable evaluations from others. Aside from directly signaling their intrinsic motivation, individuals can also choose a more aggressive strategy by demeaning extrinsic motivation (e.g., “being motivated by money is shallow and meaningless!”). Across 7 primary studies and 3 supplementary studies (N = 3153), we document the prevalence of this phenomenon, users’ (mis)perceptions of how effective this strategy should be, and its actual interpersonal consequences across different contexts. Although being extrinsically motivated is negatively evaluated, we posit that demeaning extrinsic motivation would ironically make one appear more hypocritical and thus disliked, compared to demeaning other negative behaviors or explicitly praising extrinsic motivation. Furthermore, we found that these effects are stronger for those who are low in job calling orientation and high in socioeconomic status. In sum, although people might choose to demean extrinsic motivation in order to gain social approval, such a strategy often backfires.